Cerebral blood flow abnormalities in neuropsychiatric systemic lupus erythematosus. (August 2019) - Jia, J; Xie, J; Li, H; Wei, H; Li, X; Hu, J; Meng, D; Zhang, Y; Zhang, X
Objective: To investigate the clinical characteristics, imaging changes and early diagnostic methods of neuropsychiatric systemic lupus erythematosus (NPSLE). Methods: Thirty-five SLE patients, of which 16 had overt neuropsychiatric symptoms, underwent examination for multiple autoantibodies, including anti-double-stranded DNA (anti-dsDNA) antibody, anti-nucleosome antibody, anti-cardiac-phospholipid antibody (aCL)-IgG, aCL-IgM, anti-β2-glycoprotein I antibody and anti-ribosomal P antibody, and the SLEDAI score of every patient was recorded. All patients further received neuropsychological tests, including the Mini-Mental State Examination, the Self-Rating Anxiety Scale and the Self-Rating Depression Scale. Imaging examination using 3D arterial spin labeling was performed on 3.0 T MRI scanners. After processing the 3D arterial spin labeling image, the cerebral blood flow map was obtained and the cerebral blood flow value was calculated. Results: The values of anti-dsDNA, anti-nucleosome antibody, aCL-IgG and anti-β2-glycoprotein I antibodies were significantly higher in the NPSLE group than those in the SLE group. The SLEDAI scores of the NPSLE group were significantly higher than those of the SLE group. There were no significant differences between the NPSLE group and the SLE group in the directional ability, memory, attention, numeracy, recall ability or language ability scores on the Mini-Mental State Examination scale. Furthermore, there were no symptoms of anxiety or depression in any of the patients, according to the Self-Rating Anxiety Scale and Self-Rating Depression Scale. In the 35 patients with SLE, decreases in blood perfusion were seen in some areas, and were unilateral and asymmetrically distributed. There was obvious asymmetry between sides in areas including the frontal lobe, temporal lobe, parietal lobe and occipital lobe. The incidence of perfusion decreases in frontal lobe in the NPSLE group was significantly higher than in the SLE group. Conclusion: Neurological lesions in SLE patients can be detected by arterial spin labeling. Cerebral blood flow abnormalities may be helpful for the early diagnosis of neurological lesions in NPSLE.